Analisis Pengaruh Brand Ambassador, Advertising Campaign Serta Country Of Origin Terhadap Minat Beli Pada Produk Nu Green Tea - Retnoning Ambarwati; MG Sukamdiani (STIE Wijaya Mulya, 2022)
This study aims to analyze the influence of brand ambassadors, advertising campaigns, and country of origin toward buying interest of Nu Green Tea. The data source of this research is primary data from the sample, Twitter usser who has buy Nu Green Tea. And the data collection was performed using purposive sampling by distributing questionnaires to 100 respondents. Data has been processed using SPSS Program. The results of this study indicate that: (1) there are partial effects of the brand ambassador (x1), advertising campaign (x2) and the country of origin for the purchasing (y) interest in nu green tea (2), advertaising campaign (x1) and the country of origin (3) toward the buying of nu green tea (3) the most dominant variable for buying (y) in nu green tea is the brand ambassador (x1)Keywords: brand ambassador, advertising campaign, country of origin, buying interest.